Resistência camponesa entre chapadas, carrascos e mato no Baixo Parnaíba, Maranhão - Botelho, Adielson Correia (2017)
This dissertation presents a reflection on the forms of peasant resistance to the expropriation of usufruct territories common to the advance of eucalyptus plantations in Baixo Parnaíba, Maranhão. In order to develop the research, literature review, secondary data collection, twenty-five semi-structured interviews (recorded or not) with members of peasant families and mediators (from the Catholic Church, the Union, movements and entities of civil society ). For study area, two field trips were carried out to Urbano Santos city, which helped in the empirical foundations for the study. Finally, systematization and the research report. This study demonstrated that peasants have a very complex management system of natural resource, appropriate to local ecosystems. Added to the power of social mobilization, they can reproduce socially, morally, culturally and economically. Contrary to the developmentalists, it was noticed that the advance of the eucalyptus contributed to deep changes in the daily activities of these peasants that implies the destruction of their way of life and consequently they are forced to sell their lands and their work force to companies or they will reside in the peripheries of cities.